2007
DOI: 10.1038/ncb1670
|View full text |Cite|
|
Sign up to set email alerts
|

Kif3a constrains β-catenin-dependent Wnt signalling through dual ciliary and non-ciliary mechanisms

Abstract: Primary cilia are microtubule-based organelles involved in signal transduction and project from the surface of most vertebrate cells. Proteins that can localize to the cilium, for example, Inversin and Bardet-Biedl syndrome (BBS) proteins, are implicated in both beta-catenin-dependent and -independent Wnt signalling. Given that Inversin and BBS proteins are found both at the cilium and elsewhere in the cell, the role of the cilium itself in Wnt signalling is not clear. Using three separate mutations that disru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
441
4
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(477 citation statements)
references
References 32 publications
25
441
4
2
Order By: Relevance
“…We have shown previously that suppression of some BBS proteins in zebrafish causes gastrulation defects that include shortened body axes, longer somites, and broad and kinked notochords (14,16,17,20,21). These phenotypes are consistent with abnormal planar cell polarity (PCP) signaling (21,22,24,25), which likely underlies several clinical phenotypes in patients who have BBS, including hearing defects (20), neural tube closure abnormalities (26), renal cyst formation (27), and possibly obesity and cognitive impairment (28). The fact that these observations are likely relevant to the etiopathology of BBS (20,21,(23)(24)(25), and true for all seven bbs orthologues tested (bbs1, bbs4, bbs6, bbs10, bbs12, mks1, and cep290) as well for as the three BBS modifiers mgc1203, mks3, and rpgrip1l, suggested that they might represent useful assays for all BBS genes.…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…We have shown previously that suppression of some BBS proteins in zebrafish causes gastrulation defects that include shortened body axes, longer somites, and broad and kinked notochords (14,16,17,20,21). These phenotypes are consistent with abnormal planar cell polarity (PCP) signaling (21,22,24,25), which likely underlies several clinical phenotypes in patients who have BBS, including hearing defects (20), neural tube closure abnormalities (26), renal cyst formation (27), and possibly obesity and cognitive impairment (28). The fact that these observations are likely relevant to the etiopathology of BBS (20,21,(23)(24)(25), and true for all seven bbs orthologues tested (bbs1, bbs4, bbs6, bbs10, bbs12, mks1, and cep290) as well for as the three BBS modifiers mgc1203, mks3, and rpgrip1l, suggested that they might represent useful assays for all BBS genes.…”
Section: Resultssupporting
confidence: 49%
“…These phenotypes are consistent with abnormal planar cell polarity (PCP) signaling (21,22,24,25), which likely underlies several clinical phenotypes in patients who have BBS, including hearing defects (20), neural tube closure abnormalities (26), renal cyst formation (27), and possibly obesity and cognitive impairment (28). The fact that these observations are likely relevant to the etiopathology of BBS (20,21,(23)(24)(25), and true for all seven bbs orthologues tested (bbs1, bbs4, bbs6, bbs10, bbs12, mks1, and cep290) as well for as the three BBS modifiers mgc1203, mks3, and rpgrip1l, suggested that they might represent useful assays for all BBS genes. We therefore designed translation-blocking morpholinos (MOs) against bbs1-12 ( and SI Appendix, Table S1) and injected each into WT embryos at varying concentrations to establish a survival curve (SI Appendix, Table S3) from which to derive the optimal working MO concentration (minimal cytotoxicity, maximal phenotype).…”
Section: Resultsmentioning
confidence: 86%
“…Mechanistically, conditional loss of Kif3a and IFT in the developing mouse cerebellum results in the failure of Shhdependent proliferation of granule neuron progenitors within the developing cerebellar external granule layer [44,45] (Figure 1B). Since cilia are required to process both Shh and Wnt signals in a range of cell types [46][47][48][49], it is hypothesized that the JSRD genes encode mediators of these signal transduction pathways at the primary cilium and that the primary defect in JSRD is compromised granule cell proliferation which in turn, leads to significant cerebellar hypoplasia. Axonal migration defects causing the distinctive "molar tooth" sign may also be caused by ciliary defects, however, until JSRD gene-specific knock-outs are available, these hypotheses cannot be directly tested.…”
Section: Joubert Syndrome and Related Disordersmentioning
confidence: 99%
“…By contrast, OFD1 acts at the distal ends of centrioles to control distal appendage formation and centriole length [126]. It is involved in targeting the IFT protein, IFT88, to the distal end of the centriole and possibly to the basal body [127]. Through recruitment of CEP164, a distal appendage protein mutated in cystic kidney disease, OFD1 also promotes basal body docking to the plasma membrane [114,128].…”
Section: Ciliopathies (A) Primary Cilia Formation and Centriolar Satementioning
confidence: 99%